Accounting for Recent Changes of Gain in Dealing with Ties in Iterative Methods for Circuit Partitioning - Yong-Hyuk Kim; Yourim Yoon (Discrete Dynamics in Nature and Society)
In iterative methods for partitioning circuits, there is often a choice among several modules which will all produce the largest available reduction in cut size if they are moved between subsets in the partition. This choice, which is usually made by popping modules off a stack, has been shown to have a considerable impact on performance. By considering the most recent change in the potential reduction in cut size associated with moving each module between subsets, the performance of this LIFO (last-in first-out) approach can be significantly improved.